Pyrrolidine Dithiocarbamate Might Mitigate Radiation-Induced Heart Damage at an Early Stage in Rats - Yajing Wu; Lina Liu; Shengliang Lv; Yi Wang; Shuai Wang; Sheng Wang; Jiandong Zhang; Jun Wang (Frontiers Media S.A., 2022)
Objective: Radiation-induced heart damage (RIHD) is becoming an increasing concern due to offsetting clinical benefits of radiotherapy to a certain extent. Pyrrolidine dithiocarbamate (PDTC) as an antioxidant has been implicated in cardioprotective effects. We aimed to investigate whether pyrrolidine dithiocarbamate could attenuate heart damage at an early stage post-irradiation and unveil the potential mechanisms.Methods: A total of 15 adult male Sprague-Dawley rats were randomized into the control, irradiation (IR), and PDTC plus irradiation (PDTC + IR) groups. Hearts were irradiated with a single fraction of 20.0 Gy. Rats received daily intraperitoneal injection of PDTC for 14 days. At the 14th day post-irradiation, echocardiography was performed, and rats were killed. Morphological damage was examined by hematoxylin-eosin (HE) stain and Masson's trichrome stain. The collagen volume fraction (CVF) was applied for semi-quantitative analysis. The protein levels were analyzed by Western blot and mRNA levels by quantitative real-time PCR.Results: No significant damage to systolic function of left ventricular was induced at an early stage post-irradiation. HE staining of cardiac tissue showed that the disordered arrangement of myocardial cells and abnormal cell infiltration were alleviated in the PDTC + IR group. The increased CVF in the irradiation group was inhibited in the PDTC + IR group (22.05 ± 2.64% vs. 9.99 ± 1.65%, p < 0.05). The protein levels of nuclear factor-kappa B (NF-κB), hypoxia-inducible factor-1α (HIF-1α), and COL-1 were downregulated after treatment with PDTC (p < 0.05), and there was a declining trend in the protein of the connective tissue growth factor (CTGF). The mRNA expression of NF-κB and HIF-1α in the PDTC plus irradiation group was lower than that in the irradiation group (p < 0.05), and there was a declining trend in the mRNA expression of the connective tissue growth factor and COL-1.Conclusion: PDTC alleviates myocardial cell disordered arrangement, abnormal cell infiltration, and pro-fibrotic change at an early stage in rats with radiation-induced heart damage. Such a protective effect is closely associated with the downregulation of NF-κB.